Review of COBIT-Based Information System Audits in IT Governance - Ginting, Olivia Deslovita br; Simangunsong, Samaria; Zahara, Siti; Wardhani, Neng Sri (CV Raskha Media Group, 2025)
This study aims to review the implementation of information system audits based on Control Objectives for Information and Related Technology (COBIT) in supporting information technology (IT) governance. The background of this study is based on the importance of effective and structured IT governance to ensure alignment between the use of information technology and organizational objectives. However, in practice, many organizations have not optimally implemented information system audits as part of IT governance evaluation and control. This study uses a qualitative research method with a descriptive approach, where data is collected through literature studies, document analysis, and examination of the COBIT framework as an information system audit standard. The results show that the implementation of COBIT-based information system audits COBIT can help organizations identify the maturity level of IT governance, evaluate the effectiveness of IT controls, and provide systematic recommendations for improvement. These findings confirm that the COBIT framework can be used as a comprehensive tool to support management decision-making and improve the quality of IT governance in a sustainable manner.